Nutrients collected during the Tara Pacific Expedition 2016-2018 - Pujo-Pay, Mireille; Conan, Pascal; Ghiglione, Jean Francois (PANGAEA, 2022)
The Tara Pacific expedition (2016-2018) sampled coral ecosystems around 32 islands in the Pacific Ocean, and sampled the surface of oceanic waters at 249 locations, resulting in the collection of nearly 58,000 samples. The expedition was designed to systematically study corals, fish, plankton, and seawater, and included the collection of samples for advanced biogeochemical, molecular, and imaging analysis. Here we provide data of nutrients at micromolar levels : Phosphate (PO4), Silicates (Si(OH)4), Nitrites (NO2) and Nitrate (NO3)
Keywords: nutrient; Tara Pacific Expedition